The effect of xerostomia on the quality of life of controlled and uncontrolled type 2 diabetes mellitus patients - Aprista, Sectio; Nelis, Surya; Nasia, Avina Anin; Prabowo, Yoghi Bagus (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: One of type 2 diabetes mellitus oral manifestations is xerostomia. Xerostomia can cause various problems, such as difficulty of eating, chewing and swallowing, so that it can affect the quality of life. The aim of this research is to analyze the effect of xerostomia on the quality of life of controlled and uncontrolled type 2 diabetes mellitus patients. Methods: This analytical observational cross-sectional study involving 92 subjects from type 2 diabetes mellitus patients aged 21 to 50 years (Patients of controlled and uncontrolled type 2 diabetes mellitus 46 subjects each). Xerostomia data was collected by Summated Xerostomia Inventory-Dutch Version questionnaire, while the quality of life data was collected by Xerostomia-related Quality of Life Scale (XeQoLs) questionnaire. All research data were analyzed descriptively and bivariate analysis with Chi-Square test. Results: The results showed that the quality of life of controlled and uncontrolled type 2 diabetes mellitus patients was equally low (50% in controlled type 2 DM patients and 64.9% in uncontrolled type 2 DM patients). This result showed that there is no difference between each subject groups. This also can be seen from the results of statistical tests that p = 0.193 (p>0.05), which means that there is no significant difference between the quality of life of controlled and uncontrolled type 2 diabetes mellitus patients. Conclusion: There was no effect between xerostomia of controlled and uncontrolled type 2 DM patients with their quality of life.Keywords: type 2 diabetes mellitus, xerostomia-related to quality of life, xerostomia